Estudios y diseño del sistema integral de agua potable, alcantarillado sanitario y pluvial para los sitios de la cadena, Santa Elena de la Cruz y Santa Elena de la parroquia El Progreso, cantón Pasaje, provincia de El Oro. - Molina Pineda, Johnny Ricardo (2015)
Currently on the Sites: CHAIN ​​SANTA ELENA DE LA CRUZ AND SANTA ELENA there is no system of sewage disposal, so that their needs are evacuated open pit latrines and septic tanks, and being caused poor health and environmental pollution in those sectors. The water consumed by the population does not have adequate treatment, causing intestinal diseases. The characteristics of the sector show that this project should be realized due to the low rate of basic sanitation in the sector. This situation justifies the study and design of sanitary-storm and potable water systems, proposed in this project and provide the basis for achieving the financing and execution of the work. The realization of this project will improve the conditions of the basic service Health-Sanitary Sewer and Stormwater Drinking Water; as well as contribute to control pollution generated sites: CHAIN, SANTA ELENA DE LA CRUZ AND SANTA ELENA.